Using Local Ecological Knowledge of Fishers to Reconstruct Abundance Trends of Elasmobranch Populations in the Strait of Sicily - Colloca, Francesco; Carrozzi, Virginia; Simonetti, Andrea; Di Lorenzo, Manfredi (Frontiers in Marine Science, 2020)
Fishers “local ecological knowledge” (LEK) can be used to reconstruct long-term trends of species that are at very low biomass due to overfishing. In this study, we used historical memories of Sicilian fishers to understand their perception of change in abundance of cartilaginous fish in the Strait of Sicily over the last decades. We conducted interviews with 27 retired fishers from Mazara del Vallo harbour (SW Sicily) working in demersal fisheries, using a pre-defined questionnaire with a series of open and fixed questions related to the abundance of sharks and rays. The questionnaire included specific questions about the trends they perceived in catch or by-catch of cartilaginous fish abundance between the 1940s and 2000s compared to the present. Information was gathered for 18 species, including Carcharhinidae, mesopredatory demersal sharks (Squalidae, Hexanchidae, Centrophoridae, Oxynotidae, Triakidae, Scyliorhinidae and Squatinidae) and batoids. Overall shark catches were perceived to have diminished since the early 1940s: about 95% of fishers reported the decline of commercially important species (e.g. Mustelus spp.) and indicated species that could have been depleted or locally extinced (e.g. Squatina spp., Sphyrna lewini, Mustelus asterias, etc.). Our study shows that LEK of fishers can be beneficial for reconstructing long-term population trends of exploited species when traditional standard data on fisheries catch or species relative abundance from surveys is limited or only available for recent periods. The results obtained clearly indicate the rapid and alarming decline of elasmobranchs in the Strait of Sicily highlighting the need for urgent conservation measures to be adopted.